Genetic background and window of exposure contribute to thyroid dysfunction promoted by low-dose exposure to 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin in mice. Issue 1 (December 2018) - Reale, Carla; Porreca, Immacolata; Russo, Filomena; Marotta, Maria; Roberto, Luca; Russo, Nicola; Carchia, Emanuele; Mallardo, Massimo; De Felice, Mario; Ambrosino, Concetta
Abstract Genetic and environmental factors contribute to thyroid diseases. Although still debated, 2, 3, 7, 8-tetrachlorodibenzo-p -dioxin (TCDD) is thought to induce thyroid dysfunction in humans and rodents. The data here reported point out the contribution of the exposure window and genetic background in mediating the low-dose TCDD effects on thyroid. Indeed, early (from E0.5 to PND30) and low-dose (0, 001 μg/kg/day) TCDD exposure reduced the circulating fT4 and altered the expression of thyroid specific transcripts. The role of genetic components was estimated monitoring the same markers inPax8 +/− andNkx2-1 +/− mice, susceptible to thyroid dysfunction, exposed to 0, 1 μg/kg/day TCDD from E15.5 to PND60. Haploinsufficiency of eitherPax8 orNkx2-1 genes exacerbated the effects of the exposure impairing the thyroid enriched mRNAs in sex dependent manner. Such effect was mediated by mechanisms involving the Nkx2-1/p53/p65/IĸBα pathwayin vitro andin vivo . Foetal exposure to TCDD impaired both thyroid function and genes expression while thyroid development and differentiation did not appear significantly affected. In mouse, stronger effects were related to earlier exposure or specific genetic background such as eitherPax8 or Nkx2-1 haploinsufficiency, both associated to hypothyroidism in humans. Furthermore, our data underline that long exposure time are needed to modelin vitro andin vivo results.